2016
DOI: 10.2166/wst.2016.344
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater containing Cr(VI) treatment using solar tubular reactor

Abstract: The hexavalent chromium, Cr(VI), which is generated in the electroplating process, is toxic to most organisms and potentially harmful to human health. The method generally used for remediation of wastewater containing Cr(VI) employs chemicals with high toxicity. This work proposes an alternative technology for the treatment of these wastewaters, based on photochemical reduction of Cr(VI) by alcohols under radiation, which is environmentally sustainable and economically viable. Initially, a batch reactor in lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Cr(VI) may cause lung cancer [3], epigastric pain, severe diarrhea, hemorrhage, dermatitis [4], tissue necrosis, and skin irritation [1]. For many decades, several techniques, such as reverse osmosis and direct precipitation [1], electrochemical reduction, ion exchange [7], biological treatment [8,9], coagulation, solvent extraction, membrane separation, biosorption [10][11][12], artificial radiation, and solar radiation in a tubular reactor, are being followed to remove Cr(VI) from polluted waters [13]. Among these methods, adsorption has been acknowledged to be the most economically favorable method due to its low energy consumption and high efficiency, even at a very low Cr(VI) concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Cr(VI) may cause lung cancer [3], epigastric pain, severe diarrhea, hemorrhage, dermatitis [4], tissue necrosis, and skin irritation [1]. For many decades, several techniques, such as reverse osmosis and direct precipitation [1], electrochemical reduction, ion exchange [7], biological treatment [8,9], coagulation, solvent extraction, membrane separation, biosorption [10][11][12], artificial radiation, and solar radiation in a tubular reactor, are being followed to remove Cr(VI) from polluted waters [13]. Among these methods, adsorption has been acknowledged to be the most economically favorable method due to its low energy consumption and high efficiency, even at a very low Cr(VI) concentration.…”
Section: Introductionmentioning
confidence: 99%
“…27 Studies using animal models showed that neuronal cell death occurs mainly or exclusively during the acute phase . 28,29 Nevertheless, the autonomic neurons have a high capability for axonal regrowth or sprouting. 30 and sympathetic reinnervation was reported in humans during the chronic phase of Chd after procedures such as heart transplantation and stem cell therapy.…”
Section: Evidence From Histopathology Studiesmentioning
confidence: 99%
“…In turn, the circuital current may be further augmented by combination of the MES with bioremediation processes including perchlorate reduction, denitrification and removal of many heavy metals [3][4]. For example, many industrial processes such as electroplating, tannery, paint, wood, chromite ores and water cooling systems produce heavy metals rich wastewaters containing very low organic loads [5][6][7], in addition to releasing large amounts of inorganic carbon. Recently, the feasibility of MES of acetate from CO2 sequestration as HCO3and simultaneous removal of heavy metals Cd(II) or Cu(II) from heavy metal-contaminated and organics-barren waters and wastewaters has been demonstrated [8][9].…”
Section: Introductionmentioning
confidence: 99%